2021
DOI: 10.1016/j.immuni.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Fate mapping of single NK cells identifies a type 1 innate lymphoid-like lineage that bridges innate and adaptive recognition of viral infection

Abstract: Fate mapping of single NK cells identifies a type 1 innate lymphoid-like lineage that bridges innate and adaptive recognition of viral infection Graphical abstract Highlights d Adaptive-like NK cell responses to MCMV encompass conventional and ILC1-like lineages d ILC1-like NK cells show enhanced cytokine production and splenic residency d ILC1-like NK cells show EOMES expression, target-specific cytotoxicity, and clonal expansion d ILC1-like NK cells drive cDC1 clustering and CD8 + T cell priming dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 49 publications
(70 reference statements)
2
48
0
Order By: Relevance
“…Also, Gerein et al (34) found that RRP patients with HPV11 genotyping displayed a more aggressive disease course and a lower incidence of long-term response to IFN-alpha therapy (14% of HPV11 vs. 64% of HPV6). However, a recent study by Flommersfeld et al (35) provided evidence that ILC1-like NK cells are a transcriptionally, phenotypically, and functionally distinct NK cell lineage, but they seem to not derive from NK cytotoxic cells, but from an independent lineage (36); therefore, further studies are still needed to provide evidence that the E6 and E7 oncogenes of HPV11 virus facilitate tumor immunoevasion through TGF−b1-induced conversion of NK cells. In summary, our present studies demonstrate that low-risk infection might induce secretion of TGF−b1 by papillomatosis that leads to reduced NK cell cytotoxicity through downregulating NK cell-activating receptors and consequently facilitates low-risk HPV11 persistent infection in JORRP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Gerein et al (34) found that RRP patients with HPV11 genotyping displayed a more aggressive disease course and a lower incidence of long-term response to IFN-alpha therapy (14% of HPV11 vs. 64% of HPV6). However, a recent study by Flommersfeld et al (35) provided evidence that ILC1-like NK cells are a transcriptionally, phenotypically, and functionally distinct NK cell lineage, but they seem to not derive from NK cytotoxic cells, but from an independent lineage (36); therefore, further studies are still needed to provide evidence that the E6 and E7 oncogenes of HPV11 virus facilitate tumor immunoevasion through TGF−b1-induced conversion of NK cells. In summary, our present studies demonstrate that low-risk infection might induce secretion of TGF−b1 by papillomatosis that leads to reduced NK cell cytotoxicity through downregulating NK cell-activating receptors and consequently facilitates low-risk HPV11 persistent infection in JORRP patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Flommersfeld et al. ( 35 ) provided evidence that ILC1-like NK cells are a transcriptionally, phenotypically, and functionally distinct NK cell lineage, but they seem to not derive from NK cytotoxic cells, but from an independent lineage ( 36 ); therefore, further studies are still needed to provide evidence that the E6 and E7 oncogenes of HPV11 virus facilitate tumor immunoevasion through TGF−β1-induced conversion of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent evidence in murine models shows that CD160 -ILC1 exhibit cytotoxicity against YAC-1 cells (22). In addition, certain populations of splenic ILC1-like NK cells are able to kill cells infected with murine cytomegalovirus (3,18,22,39). NK cells play a special role in antitumor surveillance and in antimicrobial defense against intracellular pathogens and viruses (39).…”
Section: Introductionmentioning
confidence: 99%
“…These data additionally augment previous evidence that human NK-DC interactions enhance DC cross-presentation of tumor antigens and provide further mechanistic insight within the TME ( 117 ). Furthermore, specific ILC subtypes may preferentially interact with DCs, as a recent study identified a group of ILC1-like NK cells characterized as CD27 + CD62L - CD160 + virus-responsive Ly49H + NK cells during mouse CMV (MCMV) infection ( 118 ). These cells exhibited transcriptional and functional signatures of both ILC1s and NK cells but interestingly were also marked by high expression of Batf3 and XCL1.…”
Section: Introductionmentioning
confidence: 99%